2009
DOI: 10.1103/physrevb.79.212412
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of angular momentum and the inverse Faraday effect

Abstract: Precession of magnetization via the inverse Faraday effect is investigated with a view of determining the fundamental limit on the precession speed. Such a limit could have important consequences for ultrafast magnetic switching. The angular momentum required for precession is shown to be supplied by the light. This indicates that there is no fundamental obstruction to magnetization reversal on the time scale of a laser pulse provided that a material with a sufficiently strong magneto-optical response can be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…One of the open questions is the evolution of the magnetic momentum of a medium excited by a laser pulse. 18,21,24 It cannot be answered without the knowledge of the laserinduced transitions, which lead to the change of the magnetic state of a system in the inverse Faraday effect experiments. In order to get a detailed insight into such transitions, we study the stimulated Raman scattering process, which has been suggested to be responsible for this effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the open questions is the evolution of the magnetic momentum of a medium excited by a laser pulse. 18,21,24 It cannot be answered without the knowledge of the laserinduced transitions, which lead to the change of the magnetic state of a system in the inverse Faraday effect experiments. In order to get a detailed insight into such transitions, we study the stimulated Raman scattering process, which has been suggested to be responsible for this effect.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] It was shown that such laser pulses act as an effective magnetic field in oxidic materials, which are weak ferromagnets [6][7][8][9][10] and even compensated antiferromagnets 12 and paramagnets. 13 However, the mechanisms of laser-induced magnetization dynamics are still poorly understood in spite of much experimental [6][7][8][9][10][11][12][13][14][15][16][17][18] and theoretical [19][20][21][22][23][24][25][26][27] effort. One of the open questions is the evolution of the magnetic momentum of a medium excited by a laser pulse.…”
Section: Introductionmentioning
confidence: 99%
“…8,11,12 Several theoretical mechanisms have been proposed, such as the optical Barnett effect or the inverse Einstein-de Haas effect, 13 light-induced circular currents in the collisionless limit, 14,15 the impulsive stimulated Ramanlike process, 8 and photonic angular momentum transfer via deflection of the scattered photons. 16 A dissipative IFE under THz irradiation has been computed for dirty metals with extrinsic spin-orbit interaction. 17,18 Also experimentally the situation is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The IFE is an optomagnetic counterpart of the magneto-optical Faraday effect, that is, the circularly polarized laser light imparts a magnetization in the material which exerts a torque on the pre-existing magnetization and assists the magnetization switching. However, although various models for the IFE have been proposed [11][12][13][14][15][16][17] there does as yet not exist any knowledge as to how the induced magnetization, or optomagnetic field arises, and even less is known about the materials dependence of the IFE. As materials specific theory is lacking it is neither known for which materials large effects are predicted nor how the IFE could be optimized to trigger reversal with minimal laser power.…”
mentioning
confidence: 99%